EFFECT OF AUDIT FIRM ATTRIBUTES ON FINANCIAL REPORTING QUALITY OF QUOTED DEPOSIT MONEY BANKS IN NIGERIA, 2009 – 2022 - Aloh, Moses Agashi (EBSU Journal of Social Sciences and Humanities, 2025)
The specific objectives of the study were audit tenure; audit report time lag; audit remuneration and audit firm age on financial reporting quality of quoted deposit money banks in Nigeria. The bank size was introduced as a control variable. Ex-post-facto research design was adopted through secondary data from audited and published financial statements of ten banks that existed during the research. Descriptive test was used to determine the characteristics of dependent and independent variables. Probability value at 0.05 significant level was developed. Correlation test and Panel analysis of Pooled, Fixed and Random effect OLS were used. Hausman specification test adopted chose Random Effect Model. The study discovered that audit tenure had positive and significant effect; audit report time lag had negative and no significant effect; audit remuneration had positive and significant effect while audit firm age had positive and no significant effect. The study concludes that all the audit firm attributes decomposed have significant influence on banks’ financial reporting quality. The study recommends that audit tenure should be maintained adequately since it has significant contribution to auditors’ quality and financial reporting quality of deposit money banks in Nigeria.